Operative Deliveries at Full Cervical Dilatation; 'Choosing Between Lesser of Two Evils': A Comparative Study of Morbidities of Vacuum Delivery and Caesarean Section - Aryal, Shreyashi; Shrestha, Deepak; Mahato, Sweta (Birat Journal of Health Sciences, 2020)
Introduction: Operative delivery at full cervical dilatation can be either a caesarean section or instrumental deliveries. Instrumental deliveries are well debated options for reducing caesarean section rates but they have their own set of maternal and fetal morbidities. CS at full dilatation of cervix is also demanding due to impacted fetal head. Choice between the two depends on the treating obstetrician. Objective: To assess perinatal morbidities between vacuum delivery and caesarean section at full cervical dilatation. Methodology: This is an observational cross-sectional comparative study done for the duration of one year from January to December 2019. Women undergoing vacuum delivery or caesarean section in full cervical dilatation were compared for maternal and neonatal morbidities. Risk factors associated with these morbidities were also assessed. The morbidities in each group were compared using Pearson's chi square test. Likelihood of morbidities in relation to risk factors was calculated using univariate logistic regression. Results: Prevalence of maternal complications in vacuum delivery was 33.3% (28) and in caesarean was 42.9% (15). Neonatal complications in vacuum delivery was 50% (42) and in caesarean was 48.6% (17). Being a referred case (OR=1.14) and a primigravida (OR=1.45) were risk factors for perinatal morbidities in vacuum delivery. Referred cases (OR=1.52), primigravidas (OR=5.90), head station lower than zero (OR=1.26) and birth weight of more than 3500 gms (OR=2.60) were associated with more number of morbidities in caesarean at full cervical dilatation.Conclusion Operative deliveries at full cervical dilatation, either vacuum or CS carry risk of maternal and neonatal morbidities. Obstetrician should make a decision keeping in mind certain risk factors like referred cases, parity, head station, number of pulls, method of delivery of head and fetal weight so that severe morbidities can be prevented.